Dr. Martha Heasley Cox
Doctor Martha Heasley Cox portrait, taken while she was a student at Arkansas College (now Lyon College). She graduated with a bachelor of arts degree. The college had fewer than 100 students at this time, and the Presbytarian Synod of Arkansas threatened to shut it down several times in the 1930s. Doctor Cox was between the ages of 14 & 18 when she was at the school.Digital copy only. No hard copy.